Review of the Japanese Journal of Evaluation Study - Sasaki, Ryoh (Journal of MultiDisciplinary Evaluation, 2006)
The Japan Evaluation Society was established in 2000. Since then, its professional journal, called Japanese Journal of Evaluation Study (JJES), has been published twice a year. These issues can be downloaded from the Society’s website (http://www.idcj.or.jp/JES). We can clearly observe several hot issues recently discussed by Japanese evaluation professionals in the journal. In this paper, three of them discussed in the 2005 issues are explained briefly.